The Role of Islamic Education in Shaping Children's Character Towards the Golden Generation 2045 (Current Research in Education: Conference Series Journal, 2024)
Education is a critical process for forming individuals who are not only intellectually capable and possess scientific and philosophical thinking abilities, but also capable of developing human and spiritual character. Islamic education is one vital component that helps shape this character. This writing aims to review and consider the important role of Islamic education in building character in children to realize Golden Indonesia 2045, a national vision to create a superior generation strong in character, high in morals, and capable of critical and creative thinking. This vision coincides with Indonesia's predicted demographic bonus in 2045, which the United Nations (2015) suggests will lead to a trend of very fast economic growth. Using a library research methodology, involving the exploration of various journals, books, and documents, the study highlights that Islamic education teaches children to be humble, patient, and kind-hearted, drawing examples from the high morals of the Prophet Muhammad SAW. Through the moral and ethical concepts embedded in Islamic education, it is hoped that the golden generation of 2045 will develop into individuals with strong character, integrity, and a commitment to goodness. They will then be able to contribute positively to society, drive positive change, and become future leaders for a better Indonesia by achieving three components of good character: moral knowing, moral feeling, and moral action.